Pleural clinic: where thoracic ultrasound meets respiratory medicine - Mariaenrica Tinè; Matteo Daverio; Umberto Semenzato; Elisabetta Cocconcelli; Nicol Bernardinello; Marco Damin; Marina Saetta; Paolo Spagnolo; Elisabetta Balestro (Frontiers in Medicine, 2023)
Thoracic ultrasound (TUS) has become an essential procedure in respiratory medicine. Due to its intrinsic safety and versatility, it has been applied in patients affected by several respiratory diseases both in intensive care and outpatient settings. TUS can complement and often exceed stethoscope and radiological findings, especially in managing pleural diseases. We hereby aimed to describe the establishment, development, and optimization in a large, tertiary care hospital of a pleural clinic, which is dedicated to the evaluation and monitoring of patients with pleural diseases, including, among others, pleural effusion and/or thickening, pneumothorax and subpleural consolidation. The clinic was initially meant to follow outpatients undergoing medical thoracoscopy. In this scenario, TUS allowed rapid and regular assessment of these patients, promptly diagnosing recurrence of pleural effusion and other complications that could be appropriately managed. Over time, our clinic has rapidly expanded its initial indications thus becoming the place to handle more complex respiratory patients in collaboration with, among others, thoracic surgeons and oncologists. In this article, we critically describe the strengths and pitfalls of our “pleural clinic” and propose an organizational model that results from a synergy between respiratory physicians and other professionals. This model can inspire other healthcare professionals to develop a similar organization based on their local setting.